Inspirations of Jan Lechoń - Urbańska, Monika (Inspiration, 2019)
From his youth, Jan Lechoń was inspired by romantic literature. His mother wanted him to be another romantic bard like Juliusz Słowacki. The mother’s ambitions were fulfilled, because Lechoń debuted as 13 years old child, and in 1921, after the release of Karmazynowy poemat, he was considered a literary revelation. Until the end of his life he remained faithful to the classic form of poems and to romantic inspirations (especially to the writings of Adam Mickiewicz, which he promoted), also subordinating them his private fates.Lechoń was increasingly distancing himself from contemporary literature, ignoring the creators of the new generation, trying to preserve the structure of pre-war Warsaw in New York in the 1950s.He died a suicide death at the same age as Mickiewicz, at the peak of his writing activity, but in emotional loneliness and a sense of internal bankruptcy.